THE ROLE OF TASK-BASED LANGUAGE TEACHING (TBLT) IN DEVELOPING CRITICAL THINKING AND PRAGMATIC COMPETENCE - Nasimova Khilola Zoir kizi (International Journal of Literature and Language Studies, 2026)
This academic article comprehensively analyzes the role of Task-Based Language Teaching (TBLT) in developing critical thinking skills and pragmatic competence among English as a Foreign or Second Language learners. Viewed through the lenses of modern psycholinguistic and sociocultural frameworks, the study examines how structured, goal-oriented tasks activate high-level cognitive processes by requiring learners to solve problems, analyze information, and make decisions. Furthermore, using a synthesis of established international literature, the paper demonstrates how target tasks create naturalistic communicative environments that foster the appropriate and contextual use of language, thereby systematically enhancing learners' pragmatic abilities.